Occurrence of colloid in pars distalis of the adenohypophysis of Indian buffalo - KHAN, MASSARAT; SAIGAL, R P; SETHI, R S (The Indian Journal of Animal Sciences, 2014)
Colloid containing follicles and acini in the hypophyseal cleft of 52 buffaloes of either sex at various ages ranging from 1 week to adult were examined by differential staining reaction and electron microscopy. The follicles storing colloid were recorded in the pars distalis throughout in aged animals, during pregnancy and follicular and luteal phase. However, it was not evidenced in any of the young buffalo calves.